2024
DOI: 10.1371/journal.pone.0296359
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, migration and phenotypic transformation of VSMC induced via Hcy related to up-expression of WWP2 and p-STAT3

Xiuyu Wang,
Na Gui,
Xing Ma
et al.

Abstract: To provide a theoretical basis for the prevention and treatment of atherosclerosis (AS), the current study aimed to investigate the mechanism underlying the effect of homocysteine (Hcy) on regulating the proliferation, migration and phenotypic transformation of vascular smooth muscle cells (VSMC) via sirtuin-1 (SIRT1)/signal transducer and activator of transcription 3 (STAT3) through Nedd4-like E3 ubiquitin-protein ligase WWP2 (WWP2). Here, Based on the establishment of ApoE-/- mouse models of high Hcy As and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…It has been demonstrated that DCA and TDCA induce the expression of the proinflammatory cytokine IL-8 ( 33 , 35 , 36 ) and promote vascular smooth muscle cell (VSMC) proliferation and migration, which are implicated in the pathogenesis of AS ( 37 ). TDCA primarily enhances its effects on the vasculature through activation of the IL-6/JAK1/STAT3 signaling pathway ( 38 40 ). However, Markus et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DCA and TDCA induce the expression of the proinflammatory cytokine IL-8 ( 33 , 35 , 36 ) and promote vascular smooth muscle cell (VSMC) proliferation and migration, which are implicated in the pathogenesis of AS ( 37 ). TDCA primarily enhances its effects on the vasculature through activation of the IL-6/JAK1/STAT3 signaling pathway ( 38 40 ). However, Markus et al.…”
Section: Discussionmentioning
confidence: 99%